Critical analysis of the effects of the digital technologies on reading and learning / Análisis crítico sobre los efectos de las tecnologías digitales en la lectura y el aprendizaje. Issue 3 (3rd July 2019) - Salmerón, Ladislao; Delgado, Pablo
Abstract: In the digital age, the introduction of digital technologies (or information and communication technologies, ICT) in classrooms is a necessary, imperative reality. However, the educational results do not seem to match the expectations generated. For this reason, this revision seeks to make up for the scant attention paid to the possible harmful effects of the use of ICT based on research and educational practice. After providing a general overview of the impact of ICT on learning, we survey the results of studies that reveal potential negative consequences of their use inside and outside the school context. We analyse their impact on both academic performance and other more specific areas, such as reading comprehension, and we stress the negative effects on so-called 'digital natives'. In short, what stands out is the importance of an evidence-based education practice which bears in mind the possible harmful effects of using ICT and bears in mind that its beneficial effects seem to rely on not only how much but also how they are used.